Analisis Produktivitas Pegawai dalam Meningkatkan Realisasi Penerimaan Pajak Kendaraan Bermotor di UPTB Pengelolaan Pendapatan Provinsi Sulawesi Tenggara Kabupaten Kolaka Timur - Wahyu Ramadhaning Bekti; Abdul Razak; Indira Yuana; Muh. Nur (Journal of Mandalika Social Science, 2026)
This study aims to describe and analyze 1) the productivity of employees at the Tax Management Unit of Southeast Sulawesi Province, East Kolaka Regency, in increasing Motor Vehicle Tax Revenue. 2) the obstacles faced in increasing employee productivity related to Motor Vehicle Tax revenue at the Tax Management Unit of Southeast Sulawesi Province, East Kolaka Regency, and 3) the efforts made to overcome the obstacles faced in increasing employee productivity related to Motor Vehicle Tax revenue at the Tax Management Unit of Southeast Sulawesi Province, East Kolaka Regency. This type of research is a qualitative descriptive study intended to obtain an overview of employee productivity in increasing the realization of Motor Vehicle Tax revenue at the Tax Management Unit of Southeast Sulawesi Province, East Kolaka Regency. This research was conducted at the Tax Management Unit of Southeast Sulawesi Province, East Kolaka Regency Office from July to August 2025. The results of the study indicate that 1) the productivity of employees at the Tax Management Unit of Southeast Sulawesi Province, East Kolaka Regency, East Kolaka Regency's efforts to increase Motor Vehicle Tax revenue are measured by indicators such as capability, improved results, work enthusiasm, self-development, quality, and efficiency. 2) Obstacles faced in increasing employee productivity related to Motor Vehicle Tax revenue at the UPTB Tax Management Office of Southeast Sulawesi Province, East Kolaka Regency, include skill levels, uneven abilities, mental attitudes, unequal education, and habits and behaviors. 3) Efforts made to overcome obstacles faced in increasing employee productivity related to Motor Vehicle Tax revenue at the UPTB Tax Management Office of Southeast Sulawesi Province, East Kolaka Regency, include continuous improvement, encouraging work quality, encouraging teamwork, and empowering Human Resources (HR).